2023
DOI: 10.1111/jnp.12304
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality technology in neuropsychological testing: A systematic review

Abstract: Neuropsychological testing aims to measure individuals' cognitive abilities (e.g. memory, attention), analysing their performance on specific behavioural tasks. Most neuropsychological tests are administered in the so-called 'paper-and-pencil' modality or via computerised protocols. The adequacy of these procedures has been recently questioned, with more specific concerns about their ecological validity, i.e. the relation between test scores observed in the laboratory setting and the actual everyday cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 139 publications
0
0
0
Order By: Relevance
“…Yet, with advances in virtual reality technology, the research landscape has expanded considerably. Virtual reality provides a more naturalistic framework for investigating cognitive processes [12,13] and attentional orienting [14] and enables a deeper understanding of how attentional processes work by exploring previously unexplored influencing factors. Thus, in a virtual reality cueing paradigm, it has been observed that when attention is directed forward or backward, response times are shorter for targets located in the front space than for those located in the rear space.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, with advances in virtual reality technology, the research landscape has expanded considerably. Virtual reality provides a more naturalistic framework for investigating cognitive processes [12,13] and attentional orienting [14] and enables a deeper understanding of how attentional processes work by exploring previously unexplored influencing factors. Thus, in a virtual reality cueing paradigm, it has been observed that when attention is directed forward or backward, response times are shorter for targets located in the front space than for those located in the rear space.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies on naturalistic VR tasks that simulate daily functions and activities. Some have used FSDs (e.g., Rand et al, 2009;Jovanoski et al, 2012;Raspelli et al, 2012;Cipresso et al, 2014;Ruse et al, 2014) while others have employed HMDs (e.g., Barnett et al, 2021;Chicchi Giglioli et al, 2021;Ouellet et al, 2018;Parsons & Barnett, 2017;Porffy et al, 2022; see also the reviews by Neguţ et al, 2016;Parsons, 2015;and Pieri et al, 2023). Regarding the Multiple Errands Test that was at first devised to be performed in reallife environments (Shallice & Burgess, 1991; see also Rotenberg et al, 2020), there are several desktop FSD versions have been implemented (Rand et al, 2009;Jovanoski et al, 2012;Raspelli et al, 2012;Cipresso et al, 2014), as well as a simplified tablet version to serve as a brief screening tool (Webb et al, 2021).…”
Section: Introductionmentioning
confidence: 99%